The military's entry into air interdiction of drug trafficking from South America - Ahart, J. L. (John L.); Stiles, Gerald; Rand eBooks (Santa Monica, CA : RAND, 1991)
This Note examines the military's participation in the air interdiction of international drug traffic. On the larger question of the effectiveness of drug interdiction efforts, the research indicates that interdiction efforts are having an impact on the drug market by diverting drug smugglers from the easier routes. The research also indicates that although the interfaces between the agencies involved in the civilian interdiction forces are highly complicated and not clearly defined, the effort is well established, experienced, and (apparently) working. Finally, the research indicates that the military's contributions to the air interdiction of drug traffic are significant, are providing positive benefits to the overall effort, and are growing in importance. Nonetheless, inserting the military forces into the established domain of civilian law enforcement agencies has produced problems, such as the inherent tension between the military philosophy of action and the civilian need for building evidence and the precise observance of procedures; civilian/military equipment mismatches; turf wars; and realization that increasing civilian/military integration could undercut the effort if the military has to pull out to deal with a national defense need.
This research "was conducted jointly under the National Security Strategies Program of Project Air Force and under the Policy and Strategy Program of RAND's Army Research Division's Arroyo Center"--Preface.
Includes bibliographical references (p. 45-46).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Cocaine industry -- South America; Drug traffic -- South America; Drug traffic -- United States; Narcotics, Control of -- South America; Narcotics, Control of -- United States; South America -- Armed Forces -- United States; United States -- Armed Forces -- South America; Electronic books